PERANAN SEKTOR PETERNAKAN DAN PERIKANAN TERHADAP PEREKONOMIAN PROVINSI RIAU: ANALISIS STRUKTUR INPUT-OUTPUT - Inna Hidayah; Syaiful Hadi; Djaimi Bakce (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The livestock and fishery sector are very important in the economy Riau Province as industrial raw material providers, employers, providers of food and source of income. This study aims to analyze the role of livestock and fishery sectors to the economy of Riau Province through input-output structure of the review. The data used is data input-output Riau Province 2012 with 18 x 18 sector classification sourced from the Bappeda of Riau Province. The Analytical method used is descriptive analysis method. The analysis showed: first,thelivestock and fishery sector contributed to the economy of high enough Riau Province. Livestock and fishery sectors contributes high arethe marine fish and other marine product sector, ground fish and other ground fish sector, livestock and other livestocks. Second,forming component output of livestock and fishery sector is driven by consumption, followed by intermediate output and export. Third, in term of input, component input of livestock and fishery sector is driven by producer surplus, followed by intermediate input and wage-salary. To encourage economic growth in the livestock and fishery sector and increase consumption and investment directly or indirectly.Effort to improve the investment indirectly trough the accumulation from accumulation of capital from producer surplus Keywords:   the role of livestock and fishery, input-output table, consumption, producer surplus.